The glucose management of gestational diabetes in the UK: a national survey - Isabelle K. Mayne; Maximilian J. Levy; Bijay Vaidya; Andrew P. McGovern (BMC Pregnancy and Childbirth)
Abstract Background There has never been a detailed assessment of the management of gestational diabetes (GDM) previously in the UK. Methods We conducted a national electronic survey (September 2022– June 2023) and mixed quantitative and qualitative analyses to evaluate glucose targets and glucose management in GDM across the UK. The response rate was 52% (73/141 National Health Service [NHS] trusts) with data covering 83 hospitals. Results Most hospitals use the National Institute for Health and Clinical Excellence (NICE) recommended glucose targets; the most common fasting target was 5.3 mmol/L (n = 70 hospitals; 84%); and the post-prandial 7.8 mmol/L 1-h target (n = 72; 92%) and 6.4 mmol/L 2-h target (n = 40; 78%). Metformin is used as the preferred first-line option for post-prandial and fasting blood glucose reduction in 84% of hospitals (with Modified-release metformin used initially in 17%). Insulin is used as the preferred first line in 28% for fasting and 19% for post-prandial glucose. In components of management not covered by national guidelines, there is wide practice variation, including insulin preparations used, starting doses, and titration rates. Standard insulin initiation doses ranged from 1–12 units for meal-time insulin and 2–20 units for basal insulin. There was a 13-fold difference in insulin titration rates from 0.3 units/day up to 4 units/day. The maximum basal insulin dose achievable during the first six weeks of titration varied from 15 to 182 units. Conclusions In GDM glucose management components not covered by national guidelines there is wide practice variation; slow insulin titration in some hospital protocols is of particular concern.